2004
DOI: 10.1002/mrm.20091
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance electrical impedance tomography at 3 tesla field strength

Abstract: Magnetic resonance electrical impedance tomography (MREIT) is a recently developed imaging technique that combines MRI and electrical impedance tomography (EIT). In MREIT, crosssectional electrical conductivity images are reconstructed from the internal magnetic field density data produced inside an electrically conducting object when an electrical current is injected into the object. In this work we present the results of electrical conductivity imaging experiments, and performance evaluations of MREIT in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Other J-based MREIT algorithms include the current constrained voltage scaled reconstruction (CCVSR) algorithm (Birgul et al 2003a) and equipotential line methods (Kwon et al 2002a, Ider et al 2003, Ozdemir et al 2004. A non-iterative equipotential line method called the curl-J algorithm was also suggested by Lee (2004). Lately Nachman et al (2007) proposed a different non-iterative algorithm using one boundary voltage and one internal distribution of |J|.…”
Section: Other J-based Algorithmsmentioning
confidence: 99%
“…Other J-based MREIT algorithms include the current constrained voltage scaled reconstruction (CCVSR) algorithm (Birgul et al 2003a) and equipotential line methods (Kwon et al 2002a, Ider et al 2003, Ozdemir et al 2004. A non-iterative equipotential line method called the curl-J algorithm was also suggested by Lee (2004). Lately Nachman et al (2007) proposed a different non-iterative algorithm using one boundary voltage and one internal distribution of |J|.…”
Section: Other J-based Algorithmsmentioning
confidence: 99%
“…Sparse data show that in this frequency range the human body is electrically very heterogeneous (26)(27)(28), hence a better knowledge is important. MR-Electrical Impedance Tomography (MR-EIT) (29)(30)(31)(32)(33)(34)(35) is an MR-based method that allows LF tissue conductivity mapping by combining MR-Current Density Imaging (MR-CDI) (36)(37)(38)(39) and Electrical Impedance Tomography (EIT) (40)(41)(42). However, the reduction of the injected current down to a non-painful level, while maintaining sufficient spatial resolution and signal to noise ratio (SNR), remains a problem.…”
Section: Introductionmentioning
confidence: 99%
“…These features could be advantageous to the magnetic resonance electrical impedance tomography (MREIT) technique, which incorporates a constant current source to an existing MR scanner, providing conductivity contrast information without using any contrast media or additional MR scan . MREIT has been steadily developed from the simulations, reconstruction algorithms, and imaging experiments of various phantoms and animals . It has now reached a stage of in vivo human imaging experiments and Kim et al recently reported the first such trial.…”
mentioning
confidence: 99%